Auxin flow-mediated competition between axillary buds to restore apical dominance - Balla, Jozef; Medveďová, Zuzana; Kalousek, Petr; Matiješčuková, Natálie; Friml, Jiří; Reinöhl, Vilém; Procházka, Stanislav (Scientific reports, 2016)
Apical dominance is one of the fundamental developmental phenomena in plant biology, which determines the overall architecture of aerial plant parts. Here we show apex decapitation activated competition for dominance in adjacent upper and lower axillary buds. A two-nodal-bud pea (Pisum sativum L.) was used as a model system to monitor and assess auxin flow, auxin transport channels, and dormancy and initiation status of axillary buds. Auxin flow was manipulated by lateral stem wounds or chemically by auxin efflux inhibitors 2,3,5-triiodobenzoic acid (TIBA), 1-N-naphtylphtalamic acid (NPA), or protein synthesis inhibitor cycloheximide (CHX) treatments, which served to interfere with axillary bud competition. Redirecting auxin flow to different points influenced which bud formed the outgrowing and dominant shoot. The obtained results proved that competition between upper and lower axillary buds as secondary auxin sources is based on the same auxin canalization principle that operates between the shoot apex and axillary bud.
Keywords: regulace genové exprese u rostlin; Plant Shoots; Plant Stems; výhonky rostlin; hrách setý; Pisum sativum; regulátory růstu rostlin; biologický transport; kyseliny indoloctové; Plant Growth Regulators; Indoleacetic Acids; Gene Expression Regulation, Plant; stonky rostlin; Plant Proteins; Biological Transport; rostlinné proteiny